Publishing agro-environmental resources as linked data. (14th August 2012) - Nešić, Saša; Rizzoli, Andrea E.; Athanasiadis, Ioannis N.
Publishing environmental resources to the linked environmental data requires resource publishers to conform to a set of universally recognised linked data principles. These principles, however, do not consider domain-specific semantics that are crucial for building a semantically unified environmental information space over the linked environmental data. In this paper we present an approach to publishing agro-environmental resources to the linked environmental data that extends the universal linked data principles by taking into account domain semantics of the agro-environmental domain. The approach relies on an underlying environmental resource model and introduces a set of publishing principles that should enable semantic integration of the linked agro-environmental resources. According to the proposed principles this integration happens over time as a result of conjoint acting of the resource providers and resource users. In order to prove feasibility of the approach we developed a supporting software system called AGROPub. In this paper we demonstrate three main use-cases of the system: The processes realised by these three AGROPub use-cases, all together, should enable the full integration of the linked agro-environmental resources into the semantically unified environmental information space.